Pengaruh Data Akuntansi Bank Umum Syariah di Indonesia: Perspektif Sebelum dan Saat COVID-19 - Sitira Novitasari; Farida Diyan Pertiwi; Muslihun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The global pandemic known as Covid-19 has impacted nearly every country, including Indonesia. In addition to its impact on the health sector, the economic realm, including Islamic Banking, is among the most affected sectors. A financial institution, known as a bank, plays a crucial role in a country's economy. The sustained performance and profitability of banks are vital for the continuous operation of Islamic banks as intermediaries. This research aims to assess the impact of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Total Assets, and Operational Costs on the Operating Income (BOPO) influencing the Return on Equity (ROE) during the Covid-19 pandemic in Islamic Commercial Banks in Indonesia. The analytical approach employed is Multiple Linear Regression Analysis. The results of the partial study, as indicated by the t-test, reveal that CAR, FDR, NPF, and Total Assets do not exert a significant effect on profitability (ROE), whereas BOPO significantly influences profitability (ROE).